2015
DOI: 10.1371/journal.pone.0124836
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Function in Phosphatidylinositol Metabolism for Mammalian Vps13 Family Proteins

Abstract: The Vps13 protein family is highly conserved in eukaryotic cells. In humans, mutations in the gene encoding the family member VPS13A lead to the neurodegenerative disorder chorea-acanthocytosis. In the yeast Saccharomyces cerevisiae, there is just a single version of VPS13, thereby simplifying the task of unraveling its molecular function(s). While VPS13 was originally identified in yeast by its role in vacuolar sorting, recent studies have revealed a completely different function for VPS13 in sporulation, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
1
26
0
2
Order By: Relevance
“…Actin filament, microtubule and intermediate filament (desmin and cytokeratin) networks are all affected . It also regulates vesicular transport, autophagy and is involved in the metabolism of phosphoinositides (PIPs) . The hVps13B protein is a peripheral membrane protein localized to the Golgi complex, is required for maintenance of the Golgi complex morphology and is essential for the normal glycosylation of proteins .…”
Section: The Complex Roles Of Vps13 Proteins In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin filament, microtubule and intermediate filament (desmin and cytokeratin) networks are all affected . It also regulates vesicular transport, autophagy and is involved in the metabolism of phosphoinositides (PIPs) . The hVps13B protein is a peripheral membrane protein localized to the Golgi complex, is required for maintenance of the Golgi complex morphology and is essential for the normal glycosylation of proteins .…”
Section: The Complex Roles Of Vps13 Proteins In Mammalian Cellsmentioning
confidence: 99%
“…27 It also regulates vesicular transport, 22,28 autophagy 29 and is involved in the metabolism of phosphoinositides (PIPs). 30 The hVps13B protein is a peripheral membrane protein localized to the Golgi complex, is required for maintenance of the Golgi complex morphology 31 and is essential for the normal glycosylation of proteins. 32 The hVps13C protein is enriched in the outer membrane of mitochondria, 8 lipid droplets 33 and, based on cell fractionation studies, in early endosomes.…”
Section: The Complex Roles Of Vps1proteins In Mammalian Cellsmentioning
confidence: 99%
“…Additionally, these regions show high homology with the N-and C-terminal regions in VPS13 family proteins [17][18][19]. Previous reports suggested that human VPS13A regulates autophagy [18] and maintains the amount of phosphatidylinositol phosphates in the Golgi and the plasma membrane [20]. In yeast, Vps13 has membrane-binding activity [21] and functions at membrane contact sites [22][23][24].…”
mentioning
confidence: 99%
“…Innym efektem powiązanym z ograniczeniem aktywności kinazy PI3K w fibroblastach pacjentów z ChAc jest spadek poziomu białka Ora1, podjednostki kanału transportującego Ca 2+ do wnętrza komórki i zmniejszony napływ jonów Ca 2+ [43,44]. Zmiany w aktywności kinazy PI3K są duże, jednakże wyciszenie VPS13A w szczurzych komórkach PC12 nie zmienia znacząco poziomu PI(3,4,5)P 3 w błonie komórkowej, zaobserwowano natomiast znaczący spadek poziomu PI(4)P [45]. Inną kinazą, której aktywność jest zmieniona u pacjentów z ChAc jest kinaza Lyn, z rodziny kinaz Src.…”
Section: Vps13aunclassified
“…lipidów. Stwierdzono, że mutant vps13∆ wykazuje zmniejszony poziom PI(4)P w błonach tworzących się spor, a w komórkach szczurzych PC12 pozbawionych genu VPS13A poziom PI(4)P jest obniżony w błonie komórkowej i w błonach aparatu Golgiego [45]. Sugeruje to, że Vps13 mógłby transportować PI(4)P lub jego prekursor PI.…”
Section: Vps13 U Drożdżyunclassified